Is genetic diagnosis a bliss or a bane in indian society? An impact on nuclear family: a case report of foetal skeletal dysplasia - Sandhu, Inder Mohan Singh; Kaur, Simranpreet; Nagpal, Madhu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Genetic counseling has been becoming an integral part of reproductive medicine practice. In area of feto-maternal medicine findings of ultrasonography are very important. Genetic counselor tries to link dots between USG findings and their genetic base. If abnormality is found, after the legal termination of pregnancy, for clinicians and patients, main concern is about its recurrence in future pregnancies. But the question arises about the acceptability of genetic risk calculations by concerned patient and her family. As in society like ours, the genetically literate population is quite low and generally not well prepared to accept and understand the risks related to genetic abnormalities. This thing makes work of genetic counselors much difficult when the genetic aberration is found in the concerned couple. This raises a question about the social acceptance of genetically different individuals who are phenotypically normal but if they open up about their abnormal genetic status there will be a risk of decrease in their social acceptability. Hereby we present a case report which forced us to pause and think about the level of depth at which we as a society reached so far to accept genetic analysis as one of the diagnostic tool in routine clinical practice.